Development and application of On-line Monitoring Device of Transformer Vibration - Yang Yongming; Duan Xu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A real time on-line transformer vibration monitoring system based on the Labview is proposed and applied in the monitoring of abnormal vibration of transformer caused by DC bias in this paper. The monitoring of the transformer body vibration and the signal online analysis can be well performed by this system. The vibration signals of the transformer body are detected by three acceleration sensors, and the signal features are studied in both the time domain and the frequency domain, which provides the data for the operation condition assessment and fault diagnostics. Combined with the background data base, a virtual instrument technology has been used to realize man machine interface and the real time multifunction and multi-channel monitoring. Compared with the previous similar installations, this monitoring system makes the best use of powerful computer, the flexibility of Labview in the instrument development, and the new data store technology. The experiment results suggest that the installation fully meets the requirements of real time monitoring. Some conclusions of transformer abnormal vibration under the condition of DC bias are gained. The system facilitates the detection of the early signs of transformer mechanical failures. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3131